2012
DOI: 10.1007/s00392-012-0496-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between inflammatory markers, oxidant–antioxidant status and intima-media thickness in prepubertal children with juvenile idiopathic arthritis

Abstract: Chronic and systemic inflammation seems to lead to early atherosclerotic abnormalities even in pre-pubertal JIA children. Substantial improvement can be obtained with 1-year of appropriate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 30 publications
3
35
0
4
Order By: Relevance
“…A combination therapy has been widely reported for JIA treatment (Tynjala et al 2011;Record et al 2011;Ramanan et al 2014), but no combination therapy with a biological product has been reported for the therapy of JIA yet. Oxidative stress was increased in JIA patients (Breda et al 2013;Lipinska et al 2015). On the other hand, JIA is the most common disease in pediatric rheumatology and characterized by chronically joint destruction and inflammation (Koos et al 2013;Abramowicz et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…A combination therapy has been widely reported for JIA treatment (Tynjala et al 2011;Record et al 2011;Ramanan et al 2014), but no combination therapy with a biological product has been reported for the therapy of JIA yet. Oxidative stress was increased in JIA patients (Breda et al 2013;Lipinska et al 2015). On the other hand, JIA is the most common disease in pediatric rheumatology and characterized by chronically joint destruction and inflammation (Koos et al 2013;Abramowicz et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Studies on serum cholesterol levels in JIA have shown conflicting results, but these studies have mainly been done in children 17 36–39. There are no previous data on insulin resistance in JIA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vlahos et al 16 found impaired endothelial function in 30 children with JIA compared to controls, and Breda et al recently found an increased carotid intima media thickness in 38 JIA children compared to controls 17. Previous studies on BP in JIA have showed contradictory findings 16–19…”
Section: Introductionmentioning
confidence: 99%
“…35 In a study performed in prepubertal children with JIA, it was found that children with JIA have, at baseline, higher levels of inflammatory markers (CRP and erythrocyte sedimentation rate), proinflammatory cytokines (including IL-1β and IL-6), total and LDL cholesterol, blood pressure, and carotid intima-media thickness when compared with healthy children. 36 Interestingly, all these elevated parameters were reversible with 1-year administration of nonsteroidal anti-inflammatory drugs and disease-modifying antirheumatic drugs. This suggests that not only does chronic, systemic inflammation result in premature development of atherosclerosis but also these changes are reversible with treatment of the inflammation.…”
Section: Alteration In Lipid Metabolismmentioning
confidence: 98%